Determination of fertilizer dose for maize in Potatomaize- T. Aman rice cropping pattern (Bangladesh Journal of Agricultural Research, 2015)
A field experiment was conducted at the Multilocation Testing Site (MLT) Sherpur, Bogra (AEZ 4) during November 2007-08 to October 2008-09 to find out a suitable fertilizer dose for maize as a succeeding crop following potato under Potato-Maize- T.Aman rice cropping pattern. The treatments were, T1: Soil test based (STB) fertilizer dose of NPKS following FRG, 2005, T2: STB of 75% recommended dose of PKS + full N, T3: STB of 50% recommended dose of PKS + full N and T4: Farmers practice. From the two years' results, it was found that the most profitable grain yield of maize (7.54 t/ha) was obtained from the treatment T2 and the lowest (6.16 t/ha) was in T4 (Farmers practice). Economic analysis showed that the treatment T2 gave the highest net return, benefit cost ratio was also higher in maize. Fertilizer dose could be reduced by 25% for N. Considering all the issues, maize was best fitted crop under Potato- Maize-T. Aman cropping sequence in AEZ 4 at MLT site Sherpur, Bogra. DOI: http://dx.doi.org/10.3329/bjar.v39i3.21990 Bangladesh J. Agril. Res. 39(3): 471-477, September 2014